RetFM-J, an ImageJ-based module for automated counting and quantifying features of nuclei in retinal whole-mounts. (May 2016) - Hedberg-Buenz, Adam; Christopher, Mark A.; Lewis, Carly J.; Meyer, Kacie J.; Rudd, Danielle S.; Dutca, Laura M.; Wang, Kai; Garvin, Mona K.; Scheetz, Todd E.; Abràmoff, Michael D.; Harper, Matthew M.; Anderson, Michael G.
Abstract: The present article introduces RetFM-J, a semi-automated ImageJ-based module that detects, counts, and collects quantitative data on nuclei of the inner retina from H&E-stained whole-mounted retinas. To illustrate performance, computer-derived outputs were analyzed in inbred C57BL/6J mice. Automated characterization yielded computer-derived outputs that closely matched manual counts. As a method using open-source software that is freely available, inexpensive staining reagents that are robust, and imaging equipment that is routine to most laboratories, RetFM-J could be utilized in a wide variety of experiments benefiting from high-throughput, quantitative, uniform analyses of total cellularity in the inner retina. Highlights: RetFM-J counts and quantifies features for all nuclei in the inner retina. RetFM-J is packaged as a freely available plugin on the open ImageJ-based platform. Protocols for dissection and H&E staining of mouse retinal whole-mounts are detailed.